Efektivitas Video Interaktif Berbasis Lumi Education Terhadap Hasil Belajar Siswa Melalui Pembelajaran Berdiferensiasi Berdasarkan Gaya Belajar - Adi Septian Jaenudin; Mario Emilzoli; Toto Fathoni (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
Each student has unique characteristics, and education plays a vital role in accommodating these differences through differentiated instruction. One student characteristic that can be facilitated is learning style, which may be addressed using various instructional strategies, including interactive videos. Interactive videos are learning media that integrate interactive features to enhance engagement and learner interaction beyond visual and auditory elements. This study aims to examine the effectiveness of interactive video use on students’ learning outcomes while considering differences in learning styles. Using a quantitative approach, this study employed a quasi-experimental design conducted at SMPN 5 Cimahi, involving 75 students selected through cluster random sampling. The participants were divided into two groups: an experimental group that used interactive videos and a control group that received conventional instruction without interactive videos. Data was collected through pretests to measure prior understanding and posttests to assess learning outcomes after instruction. Due to the non-normal distribution of the data, the Mann–Whitney and Wilcoxon tests were used to analyze differences in learning outcomes both between and within groups. The results indicate that the use of interactive videos based on Lumi Education has a significant effect on students’ learning outcomes. In contrast, the improvement in the control group was less substantial than that of the experimental group. These findings demonstrate that Lumi Education–based interactive videos are effective in enhancing students’ learning achievement within differentiated learning environments.